Phenotypic and molecular changes in nodule‐in‐nodule hepatocellular carcinoma with pathogenetic implications. Issue 4 (20th July 2018) - Rudini, Noemi; Novello, Chiara; Destro, Annarita; Riboldi, Elena; Donadon, Matteo; Viganò, Luca; Morenghi, Emanuela; Roncalli, Massimo; Di Tommaso, Luca
Abstract : Aims: Nodule‐in‐nodule (N/N) hepatocellular carcinoma (HCC) is a convincing proof of multistep hepatocarcinogenesis. In this lesion, an inner HCC develops within an outer, more differentiated, tumour, which can be rapidly taken over by the former so that N/N HCC is rarely detected. Methods and results: Ten resected N/N HCCs arising in cirrhotic background and characterized: (i) as outer lesions by early ( n = 3) and G1 ( n = 7) HCC; (ii) as inner lesions by G1 ( n = 3) and G2 ( n = 7) HCC. The largest/smallest diameters of outer and inner nodules were, respectively, 20/6 mm and 16/4 mm. We investigated vascular (CD34 and endocan), hepatocellular VEGF, GS, GPC3, HSP70 and CHC) and molecular ( TERT promoter and β ‐catenin ) changes taking place from the outer neoplastic compartment to the inner neoplastic compartment (INC). A diffuse pattern of CD34+ capillarized vessels and focal endocan immunoreactivity were major distinctive features acquired in the INC; VEGF immunoreactivity was inversely related to CD34 staining. A gain in the number of cells immunoreactive for GPC3, HSP70, and CHC, but not of GS‐immunoreactive cells, also occurred in the INC. TERT promoter mutations were seen in half of the cases in both compartments, whereas β‐catenin mutations were more rarely detectable. Conclusions: Major phenotypic changes take place in the INC of N/N HCC. TERT promoter mutations take place frequently and very early, and, in contrast to β ‐catenin mutations, do not appear to be acquired during N/N growth. These findings suggest that inner nodules represent a step further along the pathway of tumour progression, in contrast to earlier, simply initiated, lesions, and that complete neovascularisation predicts a change in HCC biology.